Improvements of TPS-porous asphalt using wax- based additives for the application on Malaysian expressway - Satis Kumar Selvadurai; Mohd Rosli Mohd Hasan; Ashiru Sani; Hiromitsu, Nakanishi; Meor Othman Hamzah; Sharvin Poovaneshvaran (Penerbit Universiti Kebangsaan Malaysia, 2021)
Porous asphalt provides a sustainable approach to reduce traffic noise at source, while at the same time offering storm-water management systems which promote infiltration and often reduce the need for a detention pool. However, porous asphalt is prone to premature deteriorations, in terms of ravelling, and air voids clogging, rendering its unpopularity as the road surfacing material for expressways construction. In this research, the comparative influences of Tough Fix (TF) and Tough Fix Hyper (TFH) additives incorporation were evaluated on the performance of Tafpack-Super modified porous asphalt mixtures (TPS-PA). The Tafpack-Super (TPS) as a modifier at 20%, and anti-stripping additives (TF and TFH) with dosages used in this study were 0.3%, and 0.15% based on the weight of asphalt binder, respectively. Initially, the PA mixtures were prepared according to a predetermined mix design, and verified based on the percentage of air voids, permeability, and connected air voids. Comprehensive experimental tests of Marshall stability, permeability, Cantabro loss, rutting resistance, and moisture induced damage resistance were performed to assess the mechanical performance of the TPS-PA mixtures. Moreover, the Texas boiling test was employed to assess the stripping potential of loose TPS-PA mixtures. The experimental results revealed that both TF and TFH are capable of improving the PA resistance against rutting, ravelling, and moisture damage. In addition, the porous asphalt with TFH anti-stripping agent incorporation exhibited a superior overall performance as compared to the PA with TF.